A review on tailoring the corrosion and oxidation properties of MoS2-based coatings. Issue 7 (26th January 2023) - Joseph, Antony; Vijayan, Athira S.; Shebeeb, C. Muhammed; Akshay, K. S.; John Mathew, Kevin P.; Sajith, V.
Abstract : This review discusses the corrosion and oxidation properties of MoS2 and MoS2 based coatings, their effect on the tribological properties of MoS2, and the recent progress in tailoring the corrosion resistance properties of MoS2 based coatings. Abstract : Two-dimensional (2D) layered molybdenum disulfide (MoS2 ) has intriguing physical, mechanical, optical, and semi-conducting properties and has the potential to be used in a variety of applications, such as sensors, semi-conductor devices, energy storage/conversion devices, etc. Due to its superior lubricating capabilities resulting from the easy shearing of its lamellar structure, MoS2 has traditionally been used as a solid lubricant and wear-resistant coating over metallic substrates. Unfortunately, its high susceptibility to corrosion and oxidation restricts its use in moist and humid environments. Oxidation profoundly affects the frictional, mechanical, semi-conducting, and optical properties of MoS2 . This article extensively reviews the current state of knowledge on the corrosion and surface oxidation mechanism in MoS2 and MoS2 -based coatings. Besides, the effect of oxidation on the frictional properties of MoS2 is also discussed. Several experiments undertaken to tailor the corrosion and oxidation properties of MoS2 -based coatings to prompt their usage under humid and moist conditions are also comprehensively reviewed here. Recent employment of MoS2 as a corrosion protective filler in organic coatings is also briefly discussed.